The Present Situation and Prospect of Day Surgery and Enhanced Recovery after Surgery in Thoracic Surgery - Cheng SHEN; Shuai CHANG; Kun ZHOU; Guowei CHE (Chinese Journal of Lung Cancer, 2020)
The good results of enhanced recovery after surgery (ERAS) combined with minimally invasive surgery are reflected in reducing the incidence of perioperative complications and shortening the length of hospitalization (LOS). It has been widely used in surgical fields of different specialties. The implementation of the day surgery mode can shorten the waiting time for patients and reduce the financial burden. Especially in thoracic surgery, the shorter the waiting time in the hospital, the more beneficial for the patient's physical and psychological recovery. With the widespread implementation of minimally invasive technology and accelerated rehabilitation procedures, the application of ERAS in thoracic surgery has made it possible for some thoracic surgery to be completed in the day surgery. This article summarizes the current application of ERAS in the field of thoracic surgery and the development prospects of day surgery models in China.